Foraging Behavior and Habitat Selection of Noack's Round-Leaf Bat (Hipposideros aff. ruber) and Conservation Implications. (December 2016) - Nkrumah, Evans E.; Vallo, Peter; Klose, Stefan M.; Ripperger, Simon P.; Badu, Ebenezer K.; Gloza-Rausch, Florian; Drosten, Christian; Kalko, Elisabeth K. V.; Tschapka, Marco; Oppong, Samuel K.
In sub-Saharan Africa, anthropogenic activities such as cocoa ( Theobroma cacao ) farming have replaced the natural forest vegetation, making agricultural environments more readily available to some species of bats. To augment bat conservation in such highly modified agro-environments, we evaluated the foraging decisions of the widely distributed Noack's round-leaf bat ( Hipposideros aff. ruber ) in a Ghanaian agro-environment for two factors: (a) foraging durations and (b) habitat selection from radio telemetry data collected from 13 bats. We hypothesized that it opportunistically selects foraging habitats in proportion to its availability. Our compositional analysis revealed, however, a nonrandom use of habitats. A ranking matrix indicated Hipposideros aff. ruber uses all available habitats but strongly preferred seminatural habitats dominated by fallow lands. Cocoa farms were predominantly used as flight paths for commuting between roosts and other nearby habitats during foraging. We observed a mean foraging duration of 109 min ( SD  = 62 min) per night for the species. In conclusion, our data suggest that (a) they are flexible in selecting all habitat types in the agro-environment but strongly preferred fallow matrices, (b) the provision of canopy trees within the agro-environment serves as flight paths for commuting from roost to habitats offering higher prey densities, and (3) the maintenance of fallow matrices as conservation units in sub-Saharan agro-environments helps augment conservation efforts of the species.